2003
DOI: 10.1148/radiol.2271020313
|View full text |Cite
|
Sign up to set email alerts
|

Brain Fiber Tracking with Clinically Feasible Diffusion-Tensor MR Imaging: Initial Experience

Abstract: Two technical challenges must be overcome before brain fiber tracking with diffusion-tensor magnetic resonance (MR) imaging can be applied to clinical practice: Imaging time must be shortened, and image distortion must be minimized. Single-shot echo-planar MR imaging with parallel imaging technique enabled both objectives to be accomplished. Twenty-three consecutive patients with brain tumors underwent MR imaging with a 1.5-T whole-body MR system. Fiber tracts on the lesion side in the brain had varying degree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
59
1
8

Year Published

2004
2004
2011
2011

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 126 publications
(70 citation statements)
references
References 26 publications
2
59
1
8
Order By: Relevance
“…DTI-based tractography is currently the only imaging method used to show white matter tracts in vivo (5,14). This technique is widely used to visualize motor, sensory, speech and visual pathways for neurosurgical planning and postoperative assessment (1,3).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…DTI-based tractography is currently the only imaging method used to show white matter tracts in vivo (5,14). This technique is widely used to visualize motor, sensory, speech and visual pathways for neurosurgical planning and postoperative assessment (1,3).…”
Section: Discussionmentioning
confidence: 99%
“…The parallel-imaging technique allows image reconstruction with half encoding steps, the advantage of which lies in its reduction in the geometric image distortion that is unique to echo-planar imaging. A total of 36 slices with a thickness of 2 mm and without interslice gaps were obtained (5,10). The DTI studies were performed at the end of the routine work-up for the pre-surgical evaluation of brain tumors at our institute with an average acquisition time of 7 min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, some reports have demonstrated cases with reversible loss of anisotropy in the white matter. Kim et al 8 and Yamada et al 22 reported that a decreased FA value on DTI did not necessarily represent direct damage to the tract but was more commonly noted to be a result of vasogenic edema and tract compression by the mass effect. Then, they believed that reversible loss of FA in cases of CSDH is incurred by the distortion of the pyramidal tract and vasogenic edema due to expansion of the hematoma.…”
Section: Discussionmentioning
confidence: 99%
“…Brain fiber tracking was performed by using software on a workstation (FuncTool; GE Healthcare). The sensory and pyramidal motor tracts were observed by the method introduced by Yamada et al 9 Fiber tractography demonstrated a markedly decreased fiber tract volume of the sensory and motor pyramidal tract on the right side. Sensory tract derangement was more prominent as compared with motor tract involvement (Fig 2).…”
mentioning
confidence: 99%